2001
DOI: 10.1097/00000542-200108000-00021
|View full text |Cite|
|
Sign up to set email alerts
|

Local Administration of Morphine for Analgesia after Iliac Bone Graft Harvest:Retracted

Abstract: Low-dose morphine applied to the harvest graft site can reduce local pain, morphine use, and chronic donor site pain after cervical spine fusion surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
8

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 14 publications
1
27
0
8
Order By: Relevance
“…Studies have suggested a reduction in donor-site pain by using different operative techniques [20][21][22][23], reconstructing the iliac crest using various materials such as coralline hydroxyapatite [24], or calcium phosphate [25] or inserting resorbable mesh [26], or bioactive ceramic spacers [27]. Many recent studies have also suggested superior short and long-term outcomes from post-operative analgesic infusion to the donor-site [18,[28][29][30][31]. A recent Cochrane Review protocol has been established to analyze this data collectively [32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested a reduction in donor-site pain by using different operative techniques [20][21][22][23], reconstructing the iliac crest using various materials such as coralline hydroxyapatite [24], or calcium phosphate [25] or inserting resorbable mesh [26], or bioactive ceramic spacers [27]. Many recent studies have also suggested superior short and long-term outcomes from post-operative analgesic infusion to the donor-site [18,[28][29][30][31]. A recent Cochrane Review protocol has been established to analyze this data collectively [32].…”
Section: Discussionmentioning
confidence: 99%
“…Die verbleibenden 17 Originalarbeiten wurden analysiert ( [36,38,39,40,41,42,43,44,45,46,47,50,51,52,53,55,56];…”
Section: Einfluss Der Studien Von Reubenunclassified
“…Macrae [18] zitierte in seiner Veröffentlichung "Chronisch postoperative Schmerzen" im British Journal of Anesthesia zwei gefälschte Arbeiten von Reuben et al [50,56]. Er schreibt: "Es gibt mehrere Arbeiten, die Vorteile der Regionalanästhesie zeigen, z.…”
Section: Analyse Von Beispielenunclassified
See 1 more Smart Citation
“…reduzieren [2]? Ist das plausibel, noch dazu, wenn Meta analysen, die ja einen kompletten Über blick über vergleichbare Studien geben, die Effektivität von Maßnahmen zur Be einflussung chronischer Schmerzen eher skeptisch beurteilen?…”
unclassified